Ein "Bibel-Skandal in Frankreich"?: vielmehr und trotz allem : ein ermutigendes Signal für die Inkulturation der Bibel in unsere Gegenwart! - Müller-Fieberg, Rita (Protokolle zur Bibel, 2003)
The recent French Bible translation published in 2001 by Bayard (Paris) and Médiaspaul (Montréal) was prepared in collaboration with 27 exegetes and 20 writers. while some people are filled with enthusiasm about its new conception, others are indignant at it. This article wants to describe what is really new in the "Bible Bayard" concerning its form and its translation principles (preference for the original meaning of a word, use of the literary language of today, legitimate plurality of translations due to the diversity of the Bible). And it finally evaluates the chances and limits.